Percepciones de la realidad de los internos rotativos de enfermería relacionado con su adaptación a las Prácticas Pre-profesionales. UEB. mayo 2022 – abril 2023 - Narváez Veloz, Hernán Rafael (2023)
The central theme of this research lies in the evaluation of the "Perceptions of the reality of rotating nursing interns related to their adaptation to the Pre- Professional Internship. UEB. May 2022 - April 2023", with the general objective of evaluating the perception and adaptation of rotating interns, in addition to determining the impact of the support of tutors and nursing staff on their performance and learning experience, to achieve this objective, a mixed methodology was implemented in a cross-sectional design, where a structured survey was administered to a sample composed of 85 rotating interns, thus collecting both qualitative and quantitative data that allowed exploring their perception, adaptation and experiences. The results obtained showed that a significant percentage of interns positively valued the support of tutors and nursing staff, which contributed significantly to solving problems that arose during the internship. In addition, it was noted that the academic supervision, programming and facilities provided by the institution were perceived positively, facilitating a good adaptation to the PPP and an adequate performance in their work. Based on these findings, it was concluded that the support of tutors and nursing staff, along with adequate supervision and programming, are crucial elements for the adaptation and performance of interns in PPPs, further highlighting that a well-balanced and collaborative environment facilitates the adaptation of interns to PPPs, thus contributing to their continued professional development in the health field. Therefore, it is recommended to reinforce mentoring and coaching programs, maintain and improve current conditions and facilities, continue to emphasize the relevance of the rotating internship, review and update curricula, and foster a culture of collaboration and mutual respect between interns and other health professionals. Key words: Pre-professional Internship, Adaptation, Mentoring, Nursing, Perception